Free Bone Grafts for Mandibular Reconstruction in Patients who have not Received Radiotherapy: The 6-cm Rule—Myth or Reality?. Issue 2 (June 2017) - Nandra, Baljeet; Fattahi, Tirbod; Martin, Tim; Praveen, Prav; Fernandes, Rui; Parmar, Sat
Bony reconstruction of the mandible after surgical resection results in improved rehabilitation and aesthetics. Composite tissue transfer has transformed reconstruction, particularly in patients who have received radiotherapy. However, there is morbidity related to free tissue transfer. Free nonvascularized bone grafts have much lower morbidity. Surgeons believe that free bone grafts greater than 6.0 cm are prone to failure. The aims of this study was to assess whether bone grafts greater than 6.0 cm in length have a high risk of failure. A retrospective study was performed on all patients who had free bone grafts greater than 6.0 cm in length at Birmingham, UK, and Florida, the United States. None of the patients received radiotherapy. A total of 14 patients had undergone bone grafts for mandibular defects greater than 6.0 cm in length; 13 of the bone grafts were successful. Of these 13, none were infected and there was radiographic evidence of bony union. Some of the patients have been dentally rehabilitated with implants. Contrary to much of the literature and many surgeons belief, our study has shown that long mandibular defects (>6.0 cm) are not a contraindication to the use of free bone grafts. Key principles to achieve success are discussed in this article.